Evaluation of Repairing Facial Depression Deformities Secondary to Lupus Erythematosus Panniculitis With Autologous Fat Grafting. Issue 7 (October 2016) - Lei, Hua; Ma, Gui-e; Liu, Zhenjun
Abstract : Background: A facial depression deformity secondary to lupus erythematosus panniculitis results from fat necrosis, which seriously alters the patients' appearance and thus affects their psychological health. Few studies have discussed the repair of depression deformities. The authors repaired depression deformities due to atrophic lesions by using autologous fat grafting to obtain volumetric restoration of the facial skin, and the authors report our outcomes. Methods: In this series, 30 depression deformities in 18 patients were repaired. The authors suctioned fat grafts from the abdomen and centrifuged them at 500× g for 2 minutes. After discarding the upper oil and bottom liquid, the middle fat was injected into the depressed areas (ie, the cheek, temple, and zygoma) by using multiplane and multitunnel injections. The patients, plastic surgeons on staff, and laypersons evaluated the cosmetic outcome of each patient. Results: No infection, subcutaneous nodules or cysts, cutaneous necrosis, blood vessel embolism, or other complications were found in any patient. Five patients had 1 injection, 5 had 2 injections, and 8 had 3 injections. All depression deformities improved. Regarding the cosmetic outcome, 33.3% of patients, 27.8% of laypersons, and 38.9% of doctors were satisfied with the results; 44.4% of patients, 55.6% of laypersons, and 50.0% of doctors were mostly satisfied. Conclusion: Autologous fat grafting can be a good choice for repairing facial depression deformities in patients with lupus erythematosus panniculitis, although 1 or more subsequent injections may be required to maintain the improved outcome.